Cross-cultural adaptation and construct validity of the Korean version of a physical activity measure for community-dwelling elderly - Choi, Bongsam (Journal of Physical Therapy Science, 2018)
[Purpose] This study aimed to cross-cultural adapt and validate the Korean version of an physical activity measure (K-PAM) for community-dwelling elderly. [Subjects and Methods] One hundred and thirty eight community-dwelling elderlies, 32 males and 106 female, participated in the study. All participants were asked to fill out a fifty-one item questionnaire measuring perceived difficulty in the activities of daily living (ADL) for the elderly. One-parameter model of item response theory (Rasch analysis) was applied to determine the construct validity and to inspect item-level psychometric properties of 51 ADL items of the K-PAM. [Results] Person separation reliability (analogous to Cronbach’s alpha) for internal consistency was ranging 0.93 to 0.94. A total of 16 items was misfit to the Rasch model. After misfit item deletion, 35 ADL items of the K-PAM were placed in an empirically meaningful hierarchy from easy to hard. The item-person map analysis delineated that the item difficulty was well matched for the elderlies with moderate and low ability except for high ceilings. [Conclusion] Cross-cultural adapted K-PAM was shown to be sufficient for establishing construct validity and stable psychometric properties confirmed by person separation reliability and fit statistics.